An LMI-based heuristic algorithm for vertex reduction in LPV systems - Sanjuan, Adrián; Rotondo, Damiano; Nejjari, Fatiha; Sarrate, Ramon (Zielona Góra: Uniwersytet Zielonogórski)
The linear parameter varying (LPV) approach has proved to be suitable for controlling many non-linear systems. However, for those which are highly non-linear and complex, the number of scheduling variables increases rapidly. This fact makes the LPV controller implementation not feasible for many real systems due to memory constraints and computational burden.
Keywords: linear parameter varying (LPV) paradigm; linear matrix inequality (LMI); Gershgorin circles; gain scheduling; controller design